Monetary Policy Dynamics and the Economic Growth of the Sub Sahara Africa (SSA) - Omolade, Adeleke; Mukolu, Obi Maureen (Journal of Entrepreneurship, Business and Economics, 2018)
The study investigated the effects of monetary policy dynamics on the economic growth of the SSA using data from thirty seven Sub Saharan African Countries. Dynamic panel data technique is used to estimate the model which described the relationship between SSA economic growth and monetary policy variables. However, macroeconomic variables such as exchange rate, inflation rate among others are included in the estimated dynamic panel model. The results show that the monetary policy rates failed to lead to sustainable growth in the SSA because of the limited effects it has in boosting domestic output. This reason is evident in the fact that the expected effect of expansionary monetary policy is limited due to weak financial deepening that is rampant in many Sub Saharan African Countries. Monetary policy approach that will not only be expansionary but exert required financial deepening that will have significant effect on the real domestic activities in the SSA should be encouraged. Research paper Keywords: Monetary policy dynamics, Dynamic panel data, Sub Sahara Africa Reference to this paper should be made as follows: Omolade, A., & Mukolu, O. M. (2018). monetary policy dynamics and the economic growth of the sub sahara africa (SSA), Journal of Entrepreneurship, Business and Economics , 6 (1), 36–58.